Ethics in the curriculum of odontological careers - Zaror Sánchez, Carlos; Vergara González, Carolina (Acta Bioethica, 2008)
A bibliographical review was performed related to the incorporation of ethics in the curriculum of an odontology career. The information compiled was processed in order to create a general suggestion around this theme, placing emphasis on its importance inside the curriculum, as well as in the objectives, content, and strategies involved in the instruction of this discipline.